A Preliminary Report on the Ferns of West Bengal,-Part Sikkim Forests and some Aspects of their Ecology - Chaudhuri, A. B. (Indian Forester, 1964)
This is a short report on the ecology and distribution of ferns that the author collected and observed mostly during the course of his inspections in the various forests of the state of West Bengal which cover very many climatological zones, viz., tropical, sUb-tropical, temprature and alpine and also very many types of rocks and soils. Common and interesting ferns occurring on alluvial tract, estuarine tract, laterite tract, terai and bhabar tracts of North Bengal, and gneiss and granite rocks and disintegrated soils have been grouped into natural habitats and altitudinal zones. Collections have been compared with sheets in various herbaria and a list of ferns prepared along with information collected from various herbaria and have finally been checked up at the national herbarium at Sihpur and at the regional herbarium at Shillong. As the ferns of the state have perhaps never been grouped into their ecological zones and natural habitats, the author feels that the article will be very helpful to the foresters of the state and North Bengal in particular. The ferns are very important and unavoidable component of ground flora of the temperate forests. They are most conspicuous among ground flora and epiphytes and form a definite association with phanerogamic flora in the forests between 5,000' and 9,000' (1500-2700m). Morphological characters, seasonal growth and production of leaves, etc. have not been studied by the author and not described in the article.